Pengertian, Ruang Lingkup, dan Proses Kebijakan Pendidikan - Saharudin Saharudin; Lubna Lubna (Departement of Mathematics Education, 2023)
This study aims to analyze the definition, scope and process of education policy. In this research, the writer uses a type of library research, namely a series of activities related to library data collection methods to obtain information data by collecting information related to the definition, scope and process of educational policy. Data sources in this research are primary data sources and secondary data sources such as books, articles, etc. The results of the research in this study are: A professional organization is an organization founded by two or more people who have the same profession to achieve a common goal. While the definition of organizational structure is a formal system that seeks to harmonize the relationship between sections and sub-sections in grouping and division of tasks, delegation of authority, coordination based on tasks and hierarchies. Educator Professional Organizations include: Indonesian Teachers Association (PGRI), Indonesian Lecturer Association (ADI), Indonesian Guidance and Counseling Association (ABKIN), Indonesian Education Graduate Association (ISPI). While the Education Personnel Organization is the Association of Indonesian Librarians (IPI).